Upregulation of Bax and Bcl-2 following prenatal cocaine exposure induces apoptosis in fetal rat brain - Xiao, DaLiao (Ivyspring International Publisher, 2008)
Cocaine abuse during pregnancy has been associated with numerous adverse perinatal outcomes. Aims: The present study was to determine whether prenatal cocaine exposure induced apoptosis and the possible role of Bcl-2 family genes in the programming cell death in fetal rat brain. Main methods: Pregnant rats were treated with cocaine subcutaneously (30 & 60 mg/kg/day) from day 15 to 21 of gestation. Then the fetal and maternal brains were isolated. Key findings: Cocaine produced a dose-dependent decrease in fetal brain weight and brain/body weight ratio (P<0.05). Apoptotic nuclei in fetal brain were increased from 2.6 ± 0.1 (control) to 8.1± 0.6 (low dose) and 10.4 ± 0.2% (high dose) (P<0.05). In accordance, cocaine dose dependently increased activities of caspase-3, caspase-8, and caspase-9 (% of control) in the fetal brain by 177%, 155%, 174%, respectively, at 30 mg/kg/day, and by 191%, 176%, 274%, respectively, at 60 mg/kg/day. In contrast, cocaine showed no effect on caspase activities in the maternal brain. Cocaine produced a dose-dependent increase in both Bcl-2 and Bax protein expression in the fetal brain, and increased the ratio of Bax/Bcl-2 at dose of 30 mg/kg/day (P<0.05). Significance: Our study has demonstrated that prenatal cocaine exposure induces apoptosis in the fetal brain, and suggested that up-regulating Bax/Bcl-2 gene expression may be involved in cocaine-induced apoptosis. The increased apoptosis of neuronal cells in the fetal brain is likely to play a key role in cocaine-induced neuronal defects during fetal development.